Unveiling the barriers to digital transformation in higher education institutions: a systematic literature review - Amando Jr. Singun (Discover Education)
Abstract This study investigates the challenges hindering the implementation of Digital Transformation (DT) in Higher Education Institutions (HEIs) by thoroughly reviewing the literature. It identifies multiple dimensions and subdimensions of these barriers to offer valuable insights to help HEIs navigate their transformation processes successfully. By doing so, they can effectively address the changing requirements of students, faculty, administration, and other stakeholders in an increasingly digital environment. This study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, synthesizing data from twenty (20) relevant peer-reviewed articles published between 2019 and 2024. The author employed NVivo and Zotero as methodological tools for coding, thematic analysis, and text mining to derive insights from the selected articles, thereby facilitating the development of a Concept-Centric Matrix of the Barriers to Digital Transformation (DT) in Higher Education Institutions (HEIs). The result of this study is summarized in a Concept-centric Matrix on Barriers to DT in HEIs consisting of nine (9) dimensions such as (i) Digital Vision, Strategy, and Policies; (ii) Digital Leadership and Management; (iii) Digital Organization; (iv) Digital Resources; (v) Digital Competence; (vi) Digital Stakeholder Management; (vii) Digital Culture; (viii) Digital Academic; and (ix) Digital Ethics. Each dimension has subdimensions of barriers (n = 80). Despite various sectors anticipating significant DT, many HEIs feel inadequately prepared to adapt because of the barriers to its implementation. The ongoing DT within HEIs reveals a complex landscape marked by various intertwined barriers that necessitate a strategic reevaluation and a commitment to fostering an inclusive, responsive educational environment.